FMRI as an outcome measure in clinical trials: A systematic review in clinicaltrials.gov. Issue 5 (4th March 2021) - Sadraee, Alaleh; Paulus, Martin; Ekhtiari, Hamed
Abstract: Introduction: More than one‐thousand trials with functional magnetic resonance imaging (fMRI) as an outcome measure were registered in clinicaltrials.gov at the time of writing this article. However, 93% of these registered trials are still not completed with published results and there is no picture available about methodological dimensions of these ongoing trials with fMRI as an outcome measure. Methods: We collected trials that use fMRI as an outcome measure in the ClinicalTrials.gov registry on 13 October 2018 and reviewed each trial's record entry. Eligible trials' characteristics were extracted and summarized. Results: In total, 1, 386 clinical trials were identified that reported fMRI in their outcome measures with fMRI as the only primary outcome in 33% of them. 82% of fMRI trials were started after 2011. The most frequent intervention was drug (pharmacological intervention) (29%). 57% of trials had parallel assignment design and 20% were designed for cross‐over assignment. For task‐based fMRI, cognitive systems (46%) based on Research Domain Criteria (RDoC) was the most frequent domain of tasks. Less than one‐third of trials (28%) registered at least one region of interest for their analysis. Food cue reactivity task, pain perception task, n‐back task, and monetary incentive delay task were recruited in more than 25 registered trials. Conclusion: The number of fMRI trials (fMRI as an outcome measure) with both task and rest protocols is growing rapidly. Our study suggests a growing need for harmonization and standardized checklists on both methods and analysis for preregistration of fMRI‐based outcomes in clinical trials. Abstract : The number of preregistered clinical trials with fMRI as an outcome measure (fMRI clinical trials) is increasing rapidly. The characteristics of fMRI clinical trials were reviewed.